Methods Delbecq To Determine The Scale Of Priorities In The Council Development Plan In The City Of Bandung - Rahman, Rizkia; Asep Hikmat; Muhamad Nur Afandi (CV. Inara, 2022)
The process of development planning in the City of Bandung on the level of the village held council development plan that aims to determine the priority program development. The purpose of this research is to know the process of the proposed program of activities and choose the program priority development through the method of delbecq. The study was conducted with a qualitative method to investigate in depth the process of determining the scale pioritas in program development, as well as the obstacles encountered in determining program priorities of development with the study of the region in the Village of Karang Pamulang Kecamatan Mandalajati Kota Bandung. Research instruments used were interviews, observation, and document study. Data analysis techniques using triangulation of data. Results of the study by using the method of delbecq in determining the scale of the development priorities in the Village of Karang Pamulang can easily program proposal development priorities with the right fit the needs of the community.